\(Fusarium fujikuroi\) WQF5 isolated from \(Cephalotaxus mannii \)Hook.f. as a producer of antibacterial agent and paclitaxel - Ngoc Tung, Quach; Hanh Nguyen, Vu Thi; Phuong Chi, Le; Quang, Tran Hong; Thao, Do Thi; Hoang Ha, Chu; Tien, Phi Quyet (Academia Journal of Biology, 2022)
Cephalotaxus mannii Hook.f is a rare medicinal plant used for the treatment of leukemia, however, its fungal endophytes with antibacterial and anticancer properties have not been exploited yet. In this study, six fungal isolates were recovered from roots of C. mannii collected in Ha Giang province, Vietnam. Among them, ethyl acetate crude extract of strain WQF5 exhibited strong antibacterial activity against 5 tested pathogens with inhibition zones ranging from 13.0 ± 0.5 mm to 20.0 ± 0.4 mm. Sulforhodamine B assay showed that WQF5 extract possessed the most potent cytotoxic activity against lung cancer A549 and breast cancer MCF7 cell lines with IC50 values of 6.9 ± 0.7 µg/mL and 23.1 ± 1.9 µg/mL, respectively. PCR-based molecular marker screening revealed that the positive hits for essential genes encoding 10-deacetylbaccatin III-10-O-acetyltransferase (dbat) and C-13 phenylpropanoyl side chain-CoA acyltransferase (bapt) involved in paclitaxel production were found in the fungal isolate WQF5. In addition, isolate WQF5, identified as Fusarium fujikuroi by morphological and ITS analysis, also produced paclitaxel as shown by HPLC-DAD analysis. This is the first report of bioprospecting endophytic fungi isolated from C. mannii, in which the capability of producing paclitaxel of endophytic fungi was also proved for the first time. These findings addressed a potent candidate for paclitaxel production and provided excellent material for further investigations of how endophytic fungi from non-Taxus plant species synthesize paclitaxel.